The Media Paradigm for Information Science - Skenderija, Sasha (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We are witnessing the revival of discussions about the theoretical core of information science. The reason for this revival is the appearance of Internet technologies and numerous "anomalies" in application of the traditional methods of information processing and transmission of the communication and information processes in cyberspace.